Extraordinary influence : how great leaders bring out the best in others - Irwin, Tim, 1949- (Gildan, 2018)
The age-old question for every leader---how do we bring out the best in those we lead? Anyone who has run a company, raised a family, lead an army, or coached a team struggles to find the key to help others excel and realize their potential. It is surprising how often we resort to criticism vs. an approach that actually results in a better worker and a better person.